A CASE STUDY ON RASADHATU VIKRUTI AND ITS SIGNIFICANT CO-RELATION WITH PRAMAN SHARIR (AYAM & VISTARA)” - Yesha A Kacha; Ajit Kumar S Wahane; Geetanjali; Nitin Kumar M Vala (International Journal For Research In Health Sciences And Nursing, 2024)
The study of the dimensions, measurements, and intricate structures of the many bodily parts and their sub-parts is the focus of the discipline known as Rachana Sharir. However, "Praman sharir" refers to the notion of our body's measures. Various Ayurvedic Samhitas have developed "Pramana Sharir" in unique ways. Anguli Pramana is one of the measurement systems used in Ayurved to determine the measurements of various parts and sub-parts of the human body, such as Ayama (height), Vistara (length from the tip of the middle finger on the right hand to the same on the left hand in extended posture, or arm span), etc. Inferring from the description of "Sama Ayam-Vistara" in Charak Samhita Viman-Sthana 8/118, In a healthy individual, Ayu (length of life), Bala (physical and mental strength), etc. are ideally at their highest if there is little gap between Ayam and Vistara. Ayu and Bala will be more or less depending on whether the difference between Ayam and Vistara rises or decreases. The relationship between Sama Ayam-Vistara and Krushata people under Rasadhatu Vikruti has been focused upon by the researcher in this study project as an unhealthy situation of a person. One of the dhatus from Saptadhatu described in Ayurved is Rasadhatu. According to statistical study, Rasadhatu Vikruti individuals' average Ayam & Vistara differences range from 2 to 4 Angula. The study's findings demonstrate the strong correlation between Rasadhatu Vikruti persons and variations in Ayam and Vistara. Therefore, the principle of "Sama Ayam-Vistara" aids us in better determining the Healthy or Unhealthy condition of an individual.